Eleven new species of the genus Indonemoura Baumann (Plecoptera: Nemouridae) from Thailand and Vietnam - Sivec, Ignac (Illiesia, 2010)
Eleven new species of Indonemoura Baumann are proposed from Thailand and Vietnam specimens and a tentative Thai record for I. javanica (Banks) is reported. New species include I. angulata sp. n., I. auberti sp. n., I. bilobata sp. n., I. chantaramongkolae sp. n., I. clavata sp. n, I. forcipata sp. n., I. horvati sp. n., I. malickyi sp. n., I. reducta sp. n., I. rostrilobata sp. n and I. tricantha sp. n. A provisional regional key for maleIndonemoura is presented, and a group of closely related species, including I. clavata, is recognized as the I. fujianensis complex.
Keywords: entomologija; entomology; new species; vrbnice; nove vrste; Plecoptera; Indonemoura; Nemouridae; Thailand; Vietnam